The International Criminal Court: The Failure of Justice - Marsili, M. (Unequal World International Conference on Human Development in the context of Current Global Challenges, 2020)
The Charter of the Nürnberg Tribunal introduced crimes against peace and crimes against humanity into international criminal law. War crimes, that include grave breaches of the Geneva Conventions and other serious violations of laws and customs applicable in armed conflict, were included upon proposal by the United States in the Rome Statute that establishes the International Criminal Court (ICC). The ICC goes beyond the limits of multilateral international criminal justice which has been applied to the Nuremberg Trials. The Rome treaty, which essentially codifies customary jus cogens war crimes, allows the ICC to exercise jurisdiction over the nationals of non-party countries if the crime is committed in the territory of a party country. The U.S., which inspired the ICC, signed but not ratified the Rome Statute, and therefore has no legal obligations arising from such signature. Since 1998, the U.S. has declined to join the ICC because its broad powers could pursue "politically motivated prosecutions of Americans", thus posing a threat to U.S. sovereignty. When in January 2015, after the State of Palestine accessed the Rome Statute, the ICC opened an investigation for alleged war crimes committed by Israel – which is not a member of ICC – the U.S. sided with the government of Tel Aviv and began undermining the credibility of the Court. In October 2016 South Africa, Burundi and The Gambia withdrew from the ICC, accusing it to be an instrument of political pressure of Western powers. When, in November 2017, the Court’s Office of the Prosecutor opened an investigation on alleged crimes committed in Afghanistan by U.S. military and civilian personnel, the U.S. stepped up efforts to de-legitimize the ICC. The U.S. stated that it wants to continue to exercise domestic jurisdiction over its nationals charged by the ICC for war crimes, thus removing them from international justice. In this way, we will return to a multilateral justice, or to the law of the strongest. Injustice anywhere is a threat to justice everywhere.